ANALISIS JENDER ATAS KITAB UQUD AL-LUJJAYN KARYA SYEIKH NAWAWI AL-BANTANI - Arifin, Miftahol (JURNAL AT-TURAS, 2015)
The book of Uqud al-Lujjayn, fi Bayan Huquq al-Zawjayn is a small book that is compiled and written by Shaykh Muhammad Nawawi Ibn Umar (1813-1897 M / 1230-1314 H), the ulama form Banten. This book has a great influence in the pesantren community, and even be used as the main reference in the relationship between husband and wife. Consequently, this book spawned a fundamental problems in the relationship between husband and wife. The main problems were discussed by Uqud al-Lujjayn often encountered very opposite with the ethical and moral values are highly respected by Islam itself. Might be a way of interpretation and background of the social system at the time this book in stacking is not in accordance with what is actually desired by the order of the Islamic doctrines.From the various views, either on the interpretation of verses of the Holy Qur’an and hadith at the book of Uqud al-Lujjayn, also with heavy use dha’if of hadith, hadith that indefinite it source or uncertain it sanad and rawi, which concluded with maudlhu hadith, so the book of Uqud al-Lujjayn is not suitable for consumption by the Muslims because it contradicts with the essence of the Islamic doctrine are considered equal between men with women. Islam does not distinguish between the sexes but that differentiate between one and another is only the piety to Allah swt. Islam also emphasizes the benefit of the people in his doctrines, so the views of women who underestimated in this book are very opposite with the spirit of Islamic doctrines itself.